KOMUNIKASI POLITIK NABI MUHAMMAD SAW TERHADAP PERJANJIAN HUDAIBIYAH (ANALISIS SURAT PERJANJIAN HUDAIBIYAH DALAM PERSPEKTIF JURNALISTIK) - Suf Kasman (Jurnal Dakwah Tabligh, 2019)
This is the art of diplomacy (rather politics itself) and in the history of mankind the treaty of Hudaibiyah is one of the most perfect paradigm of this art. It was for a reason that Allah referred to it as a “manifest victory” and a “mighty help”. The backbone of treaties concluded between Muslims and non-Muslims in the pre-modern era.This research is to investigate Prophet Muhammad pattern of communicating withindividuals and masses. Hudaibiyah treaty between Prophet Muhammad and Qoraish was a beginning of a newphase in the prophet’s journey to accomplish his mission and preach his call for thedivine faith to all nations. The prophet planned to spread the message of Islam beyond Arabia.